A retrospective study on enteric fever cases admitted to teaching hospital, jaffna in year 2009 - Mahasivam, N.; Jesudas, D.; Surenthirakumaran, R.; Murugananthan, K. (University of Jaffna, 2012)
Background and objectives: Typhoid is still a major health problem in Jaffna. Out of total number of cases, about 25% of them are from Jaffna district. The aim of the study was to describe the socio-demographic factors, clinical characteristics and completeness of notification of enteric fever cases admitted to Teaching hospital, Jaffna (JTH) in year 2009. Research Design and Methods: 452 Bed Head Tickets (BHT) with clinically diagnosed typhoid cases were included and data was extracted with pretested data extraction form by undergraduate medical graduates. Data were entered in SPSS 17 and single variate analysis was done for socio demographic factors, and clinical characteristics were compared with suspected cases surveillance definition of Epidemiology Unit of Sri Lanka. Completeness of notification was analysed by proportion of cases notified to local health authorities. Findings and Conclusions: The results showed children affected more and no difference in male: female ratio. Highest incidence was noted in Chavakacheri MOH division. The mean duration of hospital stay was 6.67 days. According to the surveillance case definition, the predominant presentations were fever (100%), cough (51.5%), anorexia (41.6%), headache (37.3%) and splenomegaly (35.4%). Other common clinical presentations which were not used in the surveillance case definition were vomiting (51.5%), abdominal pain (41.4%), diarrhea (34.1%) and hepatomegaly (65.3%). Relatively less number of patients presented malaise, constipation, coated tongue and skin rash. Manifestation of vomiting, diarrhoea, constipation and hepatomegaly were common in children than adults. Complicated clinical manifestations were recorded only in 3 patients however, no deaths occurred due to enteric fever in 2009. Only 65.5% of cases were notified to health authority. This study highlighted the age and geographical variations and also showed that the common clinical presentations were not included in the national clinical surveillance definition and only two third of the clinically diagnosed typhoid cases were notified. Introducing good hospital based clinical database could help to confirm these findings by analyzing cases presented to JTH in subsequent years and national level similar kind of studies will help to improve the case surveillance and notification.
Keywords: Salmonella; Typhoid fever; Enteric fever